e-Government as a Carrier of Context - RICHARD HEEKS (Jnl Publ. Pol 25(1), 2005, 2005)
e-Government is a global project of technology transfer taking designs from one context into a different context. Using examples of ` etransparency' projects, this paper finds that the context of design inscribed into e-government systems in both explicit and implicit ways can produce a mismatch with the context in which it is deployed. This creates a contextual collision that can often lead to e-government failure. In other cases, there is some form of accommodation between the two contexts: users may appropriate inscribed elements to their own purposes or there may even be a reciprocating accommodation leading to a viable system. Factors that shape either failure or accommodation are identified, as are the networks of interests that determine the design inscription and deployment accommodation processes. Conclusions are drawn about policy on e-government project design and development of e-government capacities; and about the relevance of developing/transitional economy cases for the literature on the sociology of technology.